Para não ser trapo no mundo: as mulheres negras e a cidade na narrativa brasileira contemporânea - Regina Dalcastagnè (Estudos de Literatura Brasileira Contemporânea)
This paper examines, in the work of Carolina Maria de Jesus and Conceição Evaristo , aesthetic and political possibilities of self - representation of black female experience in Brazilian metropolis. The city, in their books, is not just landscape or portrait, but element of subjectivation and space of empowerment, which become effective f rom the writing itself. Out of the dominant perspective in our literary canon–white, male, elitist–, Jesus and Evaristo not only rescue „untold stories‟ as well as produce new ways of thinking and expressing the relationship between city, gender, race a nd class.